Synthesis, physical, chemical and biological properties of 8-amino-7-[2-hydroxy-3- (3,4-dimethylphenoxy)propyl]-3-methylxantines - Ivanchenko, D.; Іванченко, Дмитро Григорович (My University, 2017)
The problem of searching for biologically active compounds amidst xanthine derivatives is a crucial one and an issue for long-term investigation. Aiming to enlarge the chemical library of prospective bioactive com pounds, we obtained a range of previously undescribed 8-amino derivatives of 7-[2-hydroxy-3-(3,4-dimeth ylphenoxy)propyl-1-]3-methylxanthine. 8-bromo-7-[2-hydroxy-3-(3,4-dimethylphenoxy)propyl-1-]3-methylxanthine and its chemical modification were the object of the study. PTP-M device, Elementar Vario L cube, Bruker SF-400 were used to confirm the structure of synthesized compounds. The biological effects of synthesized compounds were predicted by the Prediction of Activity Spectra for Substances (PASS) program. Antioxidant activity was determined by the 2,2-diphenyl-l-picrylhydrazyl (DPPH) method. In order to search for new biologically active compounds among xanthine derivatives, an 8-amino-7-[2- hydroxy-3-(3,4-dimethylphenoxy)propyl]-3-methylx:antines, never described before, was synthesized. The study of the reactions of 8-bromo-7-[2-hydroxy-3-(3,4-dimethylphenoxy)propyl-1-]3-methylx:anthine with primary, secondary and heterocyclic amines has shown that the substitution of the bromine atom ina posi tion 8 by the amine residue occurs by heating the reagents in aqueous dioxane or ethanol. The structure of the synthesized compounds has been proved with certainty by elemental analysis and nuclear magnetic res onance (NMR) spectroscopy. The antioxidant activity of the obtained compounds has been explored. The priorities for further search of biologically active compounds in a range of xanthine derivatives have been set out.
Keywords: synthesis; xanthine derivatives; NMR-spectroscopy; antioxidant activity